Agriculture and Artificial Intelligence - Navneet Kumar, Harleen Kaur, Mansirat Kaur (International Journal of Advanced Science and Technology, 2020)
Farming mechanization is primary worry and rising theme for every country. The total populace is expanding at a quick rate and with increment in populace the requirement for nourishment increments energetically. Conventional techniques utilized by ranchers aren’t sufficiently adequate to serve the expanding request thus they need to hamper the dirt by utilizing unsafe pesticides in an escalated way. This influence the rural practices a ton and at the last of land stays fruitless withenrichens. This review discusses diverse robotization rehearses likeInternet of Things, Wireless Communications, ML and AI, Deep learning. There were few regions that are making the issues farming areas like yield maladies, absence of capacity the executives, weed the board, absence of water system and the executives and these issues could be understood by previously said various systems. Now, there is a pressing require to disentangle the problems that is utilization of destructive pesticides, managed water system, manage on contamination and impacts on condition in horticultural exercise. Computerization of cultivating rehearses have demonstrated for build addition from dirt and its furthermore have fortified dirt ripeness. This reviews shows the efforts of multiple scientists to take a short outline related to present execution of computerization agribusiness. This review likewise examines a planned framework that could be actualized in organic ranch to blossom and leaf distinguishing proof utilizing IOT